Rare Genetic Disorders Affecting the Periodontal Supporting Tissues in Adolescence - Kapferer-Seebacher, Ines; Foradori, Lena; Zschocke, Johannes; Schilke, Reinhard (Frontiers in Dental Medicine, 2021)
In adolescents periodontal destruction may be the primary manifestation of an as yet unrecognized rare systemic disease, and it may be up to the periodontist to make the correct tentative diagnosis. Many genetic diseases that present with primary periodontal manifestations in adolescence affect immune function, sometimes with only mild or absent systemic features. They include periodontal Ehlers-Danlos syndrome (lack of attached gingiva, various connective tissue abnormalities), Papillon-Lefèvre syndrome (palmoplantar hyperkeratosis), and plasminogen deficiency (fibrin deposition within mucous membranes). Other immune disorders with severe periodontitis manifesting in adolescence are usually diagnosed in early childhood due to unmistakeable systemic features. They include Cohen syndrome (developmental disorder, truncal obesity, microcephaly), Hermansky-Pudlak Syndrome (oculocutaneous albinism, bleeding diathesis, and other systemic manifestations), glycogen storage disease type 1b, and Chediak-Higashi syndrome (pyogenic infections, albinism, and neuropathy). The structural integrity of periodontal tissue is affected in genodermatoses such as Kindler syndrome, a type of epidermolysis bullosa. In primary hyperoxaluria, inflammatory periodontal destruction is associated with renal calculi. Breakdown of periodontal tissues independent of dental plaque biofilm-induced periodontitis is found in hypophosphatasia (highly variable skeletal hypomineralization) or isolated odontohypophosphatasia, hypophosphatemic rickets and primary hyperparathyroidism. Finally, alveolar osteolysis mimicking localized periodontitis may be due to neoplastic processes, e.g. in neurofibromatosis type 1 (typical skin features including café au lait macules and neurofibromas), Langerhans cell histiocytosis (locally destructive proliferation of bone marrow-derived immature myeloid dendritic cells), and Gorham-Stout disease (diffuse cystic angiomatosis of bone).